2015
DOI: 10.1111/jmcb.12172
|View full text |Cite
|
Sign up to set email alerts
|

Simple Banking: Profitability and the Yield Curve

Abstract: How does bank profitability vary with interest rates? We present a model of a monopolistically competitive bank subject to repricing frictions and test the model's predictions using a unique panel data set on UK banks. We find evidence that large banks retain a residual exposure to interest rates, even after accounting for hedging activity operating through the trading book. In the long run, both level and slope of the yield curve contribute positively to profitability. In the short run, however, increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(59 citation statements)
references
References 55 publications
4
42
0
1
Order By: Relevance
“…They pay particular attention to the relationship between interest rates and bank profitability using both a theoretical model and empirical investigation of British banks. Our paper controls for money market conditions and confirms Alessandri and Nelson (2015)'s finding that in the short run increases in market rates compress the interest margin. This is not the main focus of the paper.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…They pay particular attention to the relationship between interest rates and bank profitability using both a theoretical model and empirical investigation of British banks. Our paper controls for money market conditions and confirms Alessandri and Nelson (2015)'s finding that in the short run increases in market rates compress the interest margin. This is not the main focus of the paper.…”
Section: Introductionsupporting
confidence: 70%
“…Compared with Albertazzi and Gambacorta (2009) and Bolt et al (2012), our paper also puts a stronger emphasis on bank balance sheet items and their interaction with macroeconomic conditions. Alessandri and Nelson (2015) examine the impact of funding costs on bank profitability. They pay particular attention to the relationship between interest rates and bank profitability using both a theoretical model and empirical investigation of British banks.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a significant relationship between bank profitability and the yield curve slope. Recently, Alessandri and Nelson (2015) show that the effect might be different in the short and the long run. In the long run, both the level and the slope of the yield curve contribute positively to profitability, while in the short run higher market rates compress interest margins, consistently with loan pricing frictions.…”
Section: Transmission Of Cnb and Ecb Monetary Policy To Banks' Capitamentioning
confidence: 99%
“…To sum up, concerning the relationship between market interest rates and the banks' net interest margins, there seems to be a tendency for the long-run effect to be more strongly positive than the short-run effect, where the empirical results, especially with respect to the short-run effect, are mixed even with respect to the direction of the effect. Alessandri and Nelson (2014) provide a theoretical model with a positive relationship between the interest rate level and the banks' net interest margin. They assume that a bank's mark-up on loans is a constant multiple of the market interest rate.…”
Section: Literaturementioning
confidence: 99%